(untitled) (Global Journal of Computer Science and Technology, 2023)
Entity matching is the field of research solving the problem of identifying similar records which refer to the same real-world entity In today s digital world business organizations deal with large amount of data like customers vendors manufacturers etc Entities are spread across various data sources and failure to correlate two records as one entity can lead to confusion Relationships and patterns would be missed Aggregations and calculations won t make any sense It is a significant data integration effort that often arises when data originate from different sources In such scenarios we understand the situation by linking records and then track entities from a person to a product etc There is appreciable value in integrating the data silos across various industries